Mechanical coupling of microtubule-dependent motor teams during peroxisome transport in Drosophila S2 cells - De Rossi, María Cecilia (2017)
Background: Intracellular transport requires molecular motors that step along cytoskeletal filaments actively dragging cargoes through the crowded cytoplasm. Here, we explore the interplay of the opposed polarity motors kinesin-1 and cytoplasmic dynein during peroxisome transport along microtubules in Drosophila S2 cells. Methods: We used single particle tracking with nanometer accuracy and millisecond time resolution to extract quantitative information on the bidirectional motion of organelles. The transport performance was studied in cells expressing a slow chimeric plus-end directed motor or the kinesin heavy chain. We also analyzed the influence of peroxisomes membrane fluidity in methyl--ciclodextrin treated cells. The experimental data was also confronted with numerical simulations of two well-established tug of war scenarios. SC Results and conclusions: The velocity distributions of retrograde and anterograde peroxisomes showed a multimodal pattern suggesting that multiple motor teams drive transport in either direction. The chimeric motors interfered with the performance of anterograde transport and also reduced the speed of the slowest retrograde team. In addition, increasing the fluidity of peroxisomes membrane decreased the speed of the slowest anterograde and retrograde teams. General Significance: Our results support the existence of a crosstalk between opposed-polarity motor teams. Moreover, the slowest teams seem to mechanically communicate with each other through the membrane to trigger transport.